Analgesia of post-operative wound with local anesthetics - A. A. Vinokurovа; V. A. Rudnov; S. G. Dubrovin (Вестник анестезиологии и реаниматологии, 2019)
The article presents the literature review devoted to the method of continuous administration of local anesthetic solutions in wound after various types of surgeries and its efficacy and safety compared to other methods of post-operative analgesia. It has been concluded that continuous infusion of local anesthetics into the post-operative wound is a safe and effective method allowing reducing consumption of opioid and non-narcotic systemic analgesics, minimizing the risk of post-operative nausea, vomit, skit itch, urine retention and other adverse events, thus providing favorable conditions for early activation of patients. Technical aspects are of critical value since the efficacy of this method depends on the place of catheterization, anesthetics concentration and rate of infusion. It is promising to investigate the efficacy of administration of various concentrations of solution and use of adjuvants.